Testosterone Protects Against Severe Influenza by Reducing the Pro-Inflammatory Cytokine Response in the Murine Lung - Tuku, Berfin; Stanelle-Bertram, Stephanie; Sellau, Julie; Beck, Sebastian; Bai, Tian; Kouassi, Nancy Mounogou; Preuß, Annette; Hoenow, Stefan; Renné, Thomas; Lotter, Hanna; Gabriel, Gülsah (Frontiers in Immunology, 2020)
Influenza A virus pathogenesis may differ between men and women. The 2009 H1N1 influenza pandemic resulted in more documented hospitalizations in women compared to men. In this study, we analyzed the impact of male sex hormones on 2009 pandemic H1N1 influenza A virus disease outcome. In a murine infection model, we could mimic the clinical findings with female mice undergoing severe and even fatal 2009 pandemic H1N1 influenza compared to male mice. Treatment of female mice with testosterone could rescue the majority of mice from lethal influenza. Improved disease outcome in testosterone treated female mice upon 2009 pandemic H1N1 influenza A virus infection did not affect virus titers in the lung compared to carrier-treated females. However, reduction in IL-1β cytokine expression levels strongly correlated with reduced lung damage and improved influenza disease outcome in female mice upon testosterone treatment. In contrast, influenza disease outcome was not affected between castrated male mice and non-castrated controls. Here, influenza infection resulted in reduction of testosterone expression in male mice. These findings show that testosterone has protective functions on the influenza infection course. However, 2009 pandemic H1N1 influenza viruses seem to have evolved yet unknown mechanisms to reduce testosterone expression in males. These data will support future antiviral strategies to treat influenza taking sex-dependent immunopathologies into consideration.